Efficacy and Safety of Direct Oral Anticoagulants in Elderly Patients With Atrial Fibrillation: A Network Meta-Analysis - Deng, Kaisheng; Cheng, Jinqun; Rao, Shufang; Xu, Huafu; Li, Lixia; Gao, Yanhui (Frontiers in Medicine, 2020)
Abstract Background: Direct oral anticoagulants (DOACs) have been widely used in patients with atrial fibrillation (AF) for antithrombotic prophylaxis, which were shown to have a favorable risk-benefit profile. However, there are no guideline for the use of DOACs in elderly patients (aged≥75years) with AF, which creates uncertainty about the optimal antithrombotic treatment in these patients. Methods: After comprehensively searching the EMBASE, PubMed and Cochrane databases, 5 phase Ⅲ randomized controlled trials involving 13017 elderly participants were included in this study. The efficacy outcome was stroke or systemic embolism and the safety outcome was major bleeding. We conducted a network meta-analysis by using Bayesian random effect model for the first time to evaluate the efficacy and safety of main DOACs (apixaban, edoxaban, rivaroxaban, dabigatran) and warfarin in elderly patients with AF. Hazard ratios (HRs) and their corresponding 95% confidence intervals (CIs) were used to assess the effect of drugs on efficacy and safety.The rank probabilities were used to reflect the hierarchy of drugs, and a larger rank probability value symbolized a better rank of drug. Results: There were no statistically significant differences among all interventions in the prevention of stroke or systemic embolism, while apixaban being the best among DOACs compared to warfarin (HR, 0.71; 95%CI: 0.33-1.50). Apixaban ranked the best (rank probabilities, 41.2%) in efficacy of drugs, followed by rivaroxaban, edoxaban, dabigatran and warfarin (rank probabilities, 31.8%, 15.9%, 10.9% and 0.2%, respectively). In reducing the risk of major bleeding, no statistically significant differences were found in all comparisons among the interventions, while apixaban being the best among DOACs too, compared to warfarin (HR, 0.64; 95%CI: 0.33-1.30). In safety, Apixaban ranked the best (rank probabilities,71.4%), followed by edoxaban, dabigatran, warfarin and rivaroxaban (rank probabilities, 21.0%, 5.8%, 0.9% and 0.8%, respectively). Conclusions: DOACs showed a lower incidence of stroke/systemic embolism and major bleeding than warfarin in antithrombotic therapy in elderly patients (aged≥75years), with apixaban being the best of those interventions. Therefore, apixaban should be given priority as anticoagulant in stroke prevention for elderly patients with AF.